Study on affordable housing issues among middle Income groups (M40) in Malaysia - Sulaiman, Muhammad Azwan; Yusof, Adilah; Alias, Muhammad Nazim; Abdullah, Mohamad Isa (UiTM Cawangan Johor, 2021)
Owning a house is an essential part of a human's fundamental needs. The establishment of affordable housing that is adequate in number and fulfils livable home standards is the major challenge in housing issues. Previous studies have found that the current interventions are insufficient in allowing average Malaysians to buy a home. The affordable housing-related issues that arise in Malaysia are not about the number of affordable houses in the market; however, it is about the availability of these houses for the middle-income groups. This study aims to investigate the issues and challenges faced by the middle-income group in dealing with affordable housing issues. This study is based on data from a sun1ey questionnaire adapted from a past research which was similar in terms of affordable housing issues among middle-income earners. The data were analysed and evaluated to rank the issues and provide recommendations. The findings suggest the establishment of an affordable housing agency to track and process affordable housing applications and approvals. The study results also suggest revising and improving the current affordable housing systems to help the middle-income groups to eventually own their first home. It is anticipated that the study can unravel the problems with affordable housing in this country.